Report of The Special Working Group on Cooperation For Backward Classes Volume I - Planning Commission (Planning Commission, 1962)
The programmes include measures of economic development, education and social and cultural activities. The most important part of the programme in the backward classes sector has been schemes which are generally termed" economic development schemes,” These relate to agriculture, cooperation, irrigation, small industries communication etc. In the past, for a variety of reasons, the weaker sections of the population have not in the normal course been able to secure fair share of benefits from the provisions made in the general sectors. The special schemes in the backward classes sector are intended to supplement and intensify measures of economic development to bring them, the weaker sections, upto the general level.
Government of India Ministry of Home Affairs
Government of India Ministry of Home Affairs